(3GdeUHGM GdefjQ aj ZQjH GdTQM GdcHjQs - (3CHh GdYHGS TeS GdOjf CMeO Hf eMeO Hf Ydj Gdajheis; (3GdQGaYj , CHh GdbGSe YHO GdcQje Hf eMeO Hf YHO GdcQje GdQGaYj GdbRhjfj, GdQGaYj GdbRhjfj,J (B623 (3g` s
(3ChdgG (B:s
(3bGd GdYHO GdabjQ Gdajhei GdMeO ddg QH GdYGdejf hHYO , aEfi cfJ LeYJ cJGHkG ai ZQjH TQM GdhLjR ddQGaYi s
(3BNQgG (B:s
(3bGd GHf GdCKjQ ai GdeKd GdSGFQ (B: (3djS GdaGVd ef dG jZdW , Hd GdaGVd ef jYO ZdWg hfSCd Gddg MSf GdYGbHI ai GdOfjG hGdBNQI hCf jfaY Hg WGdHg hGdfGXQ ajg s
(3GdfSNI HgG MhGTs
(3LeY ajg ZQjH TQM GdhLjR ddQGaYi hCVGa EdjgaQZ ef JCdjag SfI (B734s
(3cJHJ HNW eged GdfbW CMjGfkGHgG fXGe GdJYbjHIYdi MhGTjgG JbjjOGJs
(3HOGNdgG JUhjHGJ ddeDda s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GddZIs